Exhibition layout, values, and benefits of tourism of two crafts museums. Issue 4 (19th May 2018) - Li, Chun-Ju; Lin, Shin-Yi
Abstract: Since 2003, Taiwanese government aggressively promoted industrial tourism development for facing the economic structures challenges; moreover, the enhancement of tourist values through various software and hardware exhibitions and services are crucial topics for tourism factory tourism developments. The purpose of this study was to evaluate the values and benefits associated with factory tourism. Evaluation items were used to investigate the influence of implications in exhibition layout on tourist values and its effect on the benefits of tourism. Two crafts museums, the winners of 'excellent tourism factory', were investigated. The results show that exhibit experience, service management, and theme design reached significance in value which functional value exerted the most influence on the benefits of tourism. Also, findings of the relationship between exhibit layout and factories suggested that individual strengths, strengthening insufficiencies, and reviewing exhibition layout items that optimally generate tourist values and benefits is conducive to improved resource investment planning.